2014
DOI: 10.5665/sleep.3590
|View full text |Cite
|
Sign up to set email alerts
|

The Circadian Clock Gene Csnk1e Regulates Rapid Eye Movement Sleep Amount, and Nonrapid Eye Movement Sleep Architecture in Mice

Abstract: These results demonstrate a role for Csnk1e in regulating not only the timing of sleep, but also the REM sleep amount and NREM sleep architecture, and support Csnk1e as a causal gene in the sleep QTL on chromosome 15.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 43 publications
(51 reference statements)
4
10
0
Order By: Relevance
“…This study shows the ability of gabapentin to increase baseline von Frey thresholds in naïve mice from the two progenitor strains, indicating that Cacna2d1 is a reasonable candidate gene for basal mechanosensation, and that the effect is genotype-dependent as expected from previous studies (Chesler et al 2003a; Rode et al 2007; Zhou et al 2014). Prior studies have shown that Cacna2d1 expression is increased in the DRG and dorsal horn of the spinal cord after nerve injury (Costigan et al 2002; Field et al 2000, 2006; Luo et al 2002; Matsumoto et al 2006) and this increase has been shown to be essential to the development of mechanical, but not thermal, hypersensitivity after nerve injury (Patel et al 2013).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This study shows the ability of gabapentin to increase baseline von Frey thresholds in naïve mice from the two progenitor strains, indicating that Cacna2d1 is a reasonable candidate gene for basal mechanosensation, and that the effect is genotype-dependent as expected from previous studies (Chesler et al 2003a; Rode et al 2007; Zhou et al 2014). Prior studies have shown that Cacna2d1 expression is increased in the DRG and dorsal horn of the spinal cord after nerve injury (Costigan et al 2002; Field et al 2000, 2006; Luo et al 2002; Matsumoto et al 2006) and this increase has been shown to be essential to the development of mechanical, but not thermal, hypersensitivity after nerve injury (Patel et al 2013).…”
Section: Discussionsupporting
confidence: 82%
“…The neuropathic pain medications gabapentin and pregabalin reduce neuronal excitability and neurotransmission of affected neurons by acting at the VGCC 2 / 1 subunit encoded by Cacna2d1, and thereby, counter mechanical allodynia in neuropathic pain patients and animal models of neuropathic pain (Bian et al 2006;Field et al 2000Field et al , 2006Joshi & Taylor 2006). This study shows the ability of gabapentin to increase baseline von Frey thresholds in naïve mice from the two progenitor strains, indicating that Cacna2d1 is a reasonable candidate gene for basal mechanosensation, and that the effect is genotype-dependent as expected from previous studies (Chesler et al 2003a;Rode et al 2007;Zhou et al 2014). Prior studies have shown that Cacna2d1 expression is increased in the DRG and dorsal horn of the spinal cord after nerve injury (Costigan et al 2002;Field et al 2000Field et al , 2006Luo et al 2002;Matsumoto et al 2006) and this increase has been shown to be essential to the development of mechanical, but not thermal, hypersensitivity after nerve injury (Patel et al 2013).…”
Section: Discussionsupporting
confidence: 64%
“…The hourly mean number of bouts is not shown but can be inferred from the other metrics. In general, the profiles are very similar to those seen in the literature (Brankačk et al 2010, Martire et al 2012, Zhou et al 2014). …”
Section: Resultssupporting
confidence: 85%
“…While evidence suggests that some of these genes, such as Sik3, have nonoverlapping effects on sleep or circadian systems, there are also variants of genes that not only regulate circadian rhythms (e.g., PER3) but also can modulate sleep (Viola et al 2007). Hinting at how this may disclose neural circuitry that converges between sleep and timing systems, ablation of clock genes (e.g., in CLOCK mutant mice) (Naylor et al 2000) or circadian-associated genes such as Vip also alters sleep duration or structure (Naylor et al 2000;Wisor et al 2002;Laposky et al 2005;Hu et al 2011;Zhou et al 2014). However, in many such studies conducted to date, the genetic targeting has been unspecific with regard to the involved cell types and timing of the deletion (to exclude developmental effects).…”
Section: Overlapping Genetics Of Sleep and Circadian Rhythms?mentioning
confidence: 99%